Implentasi Program KBS Dalam Meningkatkan Kesejahteraan Masyarakat - Suryanto (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Background: Social welfare is highly correlated with health because poor health can cause a decrease in the level of social welfare and vice versa. Some of the indicators used to measure the level of community welfare include; Life Expectancy (AHH), Average Years of Schooling and Per-Capital Expenditures from the community. This is consistent with the results of research by Erwin Ndakularak, et al (2013) who concluded that household expenditures for food, education and health simultaneously have a significant effect on the welfare of the people of districts/cities in the Province of Bali. From the description above, it is deemed necessary to analyze the benefits of the KBS program in improving the welfare of the people of Badung Regency..